What Comprises a Successful Educational Science YouTube Video? A Five-Thousand User Survey on Viewing Behaviors and Self-Perceived Importance of Various Variables Controlled by Content Creators - Beautemps, Jacob; Bresges, André (Frontiers in Communication, 2021)
Educational videos on digital platforms are an attractive way of learning, especially for the younger generation, as they provide easy, personalizable access to a wide variety of content. Allowing for simplified explanations and visual demonstrations, educational videos are highly suitable for scientific content. With 500 h of video content uploaded per minute, YouTube is the most used user-generated video content platform worldwide. This study provides an initial insight into the elements which influence the perceived quality of educational science videos by viewers, with a special focus on natural science videos. In response to a call for study participants via various German natural science and technology YouTube and Instagram channels, over 5,000 participants between the ages of 9 to 72 (M = 18, SD = 8.78) completed a web questionnaire. The questionnaire focused on the participants’ viewing behaviors and their self-perception of the importance of the content-creator controlled variables.It was found that there are six key elements for a successful educational YouTube video: 1) structure, 2) reliability, 3) quality, 4) community integration, 5) presenter, 6) topic. Based on these elements, a checklist with 17 recommendations for the creation of successful educational videos was developed, serving as a practical guideline for content creators.